Binjai Train Ticket Counter Queue Simulation Using Weibull Service Distribution - Refirda Agtalia; Akim M H Pardede; Magdalena Simanjuntak (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
This research aims to improve the efficiency of train ticket counter services at Binjai Station through the use of Weibull service distribution-based queuing simulations. Long queues and excessive waiting times are often problems at many train stations, and this research aims to address these problems.This study collects queuing data from train ticket booths at Binjai Station over a certain period and analyzes them to identify existing queuing patterns. The Weibull service distribution was chosen as the appropriate model to describe the ticket counter service time, because this distribution has the flexibility to handle variations in service time well.   Queue simulation is carried out using simulation software that models the queuing process at the train ticket counter. Weibull distribution parameters are integrated into the simulation to predict service time at the ticket counter. In this simulation, various scenarios and strategies for improving service efficiency are evaluated to identify the best alternative that can be implemented at Binjai Station. The results of this study will provide guidance to the management of the Binjai train station in making decisions regarding increasing the efficiency of ticket counter services. By optimizing service time and reducing customer waiting time, it is expected to increase customer satisfaction and operational efficiency of train stations.